2023
DOI: 10.3389/fimmu.2022.947136
|View full text |Cite
|
Sign up to set email alerts
|

The genetic and epigenetic regulation of CD55 and its pathway analysis in colon cancer

Abstract: BackgroundCD55 plays an important role in the development of colon cancer. This study aims to evaluate the expression of CD55 in colon cancer and discover how it is regulated by transcriptional factors and miRNA.MethodsThe expression of CD55 was explored by TIMER2.0, UALCAN, and Human Protein Atlas (HPA) databases. TRANSFAC and Contra v3 were used to predict the potential binding sites of transcription factors in the CD55 promoter. TargetScan and starBase v2.0 were used to predict the potential binding ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Subsequent studies found CD55 is amplified in breast, colon, gastric, lung, renal, thyroid, brain, cervical, and ovarian cancers [ 6 ]. Recent studies show that cancer cells utilize CD55 to promote cell proliferation and survival [ 7 ]. Mechanistically, CD55 accelerates tumor growth by activating oncogenic pathways including JNK, LCK/FYN, JAK/STAT3, and NF-kB/MAPK in several cancers [ 3 , 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies found CD55 is amplified in breast, colon, gastric, lung, renal, thyroid, brain, cervical, and ovarian cancers [ 6 ]. Recent studies show that cancer cells utilize CD55 to promote cell proliferation and survival [ 7 ]. Mechanistically, CD55 accelerates tumor growth by activating oncogenic pathways including JNK, LCK/FYN, JAK/STAT3, and NF-kB/MAPK in several cancers [ 3 , 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that cancer cells utilize CD55 to promote cell proliferation and survival [ 7 ]. Mechanistically, CD55 accelerates tumor growth by activating oncogenic pathways including JNK, LCK/FYN, JAK/STAT3, and NF-kB/MAPK in several cancers [ 3 , 7 9 ]. Ovarian CSCs express high levels of CD55 and shRNA mediated silencing in ovarian cancer cells leading to attenuation of self-renewal and increased cisplatin sensitivity [ 3 ].…”
Section: Introductionmentioning
confidence: 99%